Employee involvement in companies under the European Company Statute - Rehfeldt, Udo; Voss, Eckhard; Pulignano, Valeria; Kelemen, Melinda; Telljohann, Volker; Fulton, Lionel; Mester, Dániel; Schütze, Kim; Wilke, Peter; Neumann, László (Luxembourg, 2011)
"The European Company Statute (SE) is based on the Council Regulation on the Statute for a European Company (2157/2001/EC) and on the Directive supplementing the Statute for a European Company with regard to the involvement of employees (2001/86/EC). It is one of the most important pieces of company legislation published so far by the European Union. Adopted in 2001, it has since October 2004 made it possible for companies operating in more than one EU Member State to reorganise their cross-border business under a single European label. This enables them to work under the umbrella of a single legal framework, thereby reducing the internal costs of operating in several countries. Employee involvement, including participation rights at board level, is the focus of this research report."